2007
DOI: 10.1002/bjs.5571
|View full text |Cite
|
Sign up to set email alerts
|

Geographic origin of publications in surgical journals

Abstract: The USA is the most productive country in terms of absolute number of surgical publications in the selected journals. However, when population size is taken into consideration, certain smaller European countries were more prolific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…This analysis has demonstrated the leading role which the United States plays in breast cancer research, a finding previously noted in other scientific disciplines [22,23]. This is not surprising given the enormous No.…”
Section: Discussionsupporting
confidence: 71%
“…This analysis has demonstrated the leading role which the United States plays in breast cancer research, a finding previously noted in other scientific disciplines [22,23]. This is not surprising given the enormous No.…”
Section: Discussionsupporting
confidence: 71%
“…Van Rossum et al [4] examined the world scientific contribution in the field of surgical research through a bibliometric study and reported that Australia appear to be inferior to some European countries, the United States and the United Kingdom in terms of publications per 10 6 inhabitants, total number of publications and publication mean IF. Nonetheless, it is encouraging to note that there has been an increase in the number of papers published annually in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…King analysed the numbers of published general scientific research papers (ranging from clinical medicine to engineering) [4]. Within clinical medicine, more specific studies have been undertaken in such disciplines as general surgery, anaesthesia and respiratory medicine [5][6][7] 2 There is a non-linear relationship between economic wealth (as measured by GDP per capita) and populationadjusted output of ophthalmic research. Countries with a per capita GDP greater than $20,000 (US) publish significantly more per capita, with Singapore, Israel and the UK prolific, while countries such as Ireland, the US and Norway are publishing at a lower than expected rate output, comparing the contribution of the developing and developed worlds [8][9][10].…”
Section: Discussionmentioning
confidence: 99%